Power, policy and the Prunus africana bark trade, 1972–2015. (3rd February 2016) - Cunningham, A.; Anoncho, V.F.; Sunderland, T.
Abstract: Ethnopharmacological relevance: After almost 50 years of international trade in wild harvested medicinal bark from Africa and Madagascar, the example of Prunus africana holds several lessons for both policy and practice in the fields of forestry, conservation and rural development. Due to recent CITES restrictions on P. africana exports from Burundi, Kenya and Madagascar, coupled with the lifting of the 2007 European Union (EU) ban in 2011, Cameroon's share of the global P. africana bark trade has risen from an average of 38% between 1995 and 2004, to 72.6% (658.6 metric tons) in 2012. Cameroon is therefore at the center of this international policy arena. Methods and materials: This paper draws upon several approaches, combining knowledge in working with P. africana over a 30-year period with a thorough literature review and updated trade data with "ground-truthing" in the field in 2013 and 2014. This enabled the construction of a good perspective on trade volumes (1991–2012), bark prices (and value-chain data) and the gaps between research reports and practice. Two approaches provided excellent lenses for a deeper understanding of policy failure and the "knowing-doing gap" in the P. africana case. A similar approach toMédard's (1992) analyses of power, politics and African development was taken and secondly, studies of commodity chains that assess the power relations that coalesce around different commodities (Ribot, 1998 ;Ribot and Peluso, 2003 ). Results: Despite the need to conserve genetically and chemically diverse P. africana, wild populations are vulnerable, even in several "protected areas" in Burundi, Cameroon, the Democratic Republic of Congo and in the forest reserves of Madagascar. Secondly, hopes of decentralized governance of this forest product are misplaced due to elite capture, market monopolies and subsidized management regimes. At the current European price, for P. africana bark (US6 per kg) for example, the 2012 bark quota (658.675 t) from Cameroon alone was worth over US3.9 million, with the majority of this accruing to a single company. In contrast to lucrative bark exports, the livelihood benefits and financial returns to local harvesters from wild harvest are extremely low. For example, in 2012, the 48 active harvesters working within Mount Cameroon National Park (MCNP) received less than 1US per day from bark harvests, due to a net bark price of 0.33 US per kg (or 43% of the farm gate price for wild harvested bark). In addition, the costs of inventory, monitoring and managing sustainable wild harvests are far greater than the benefits to harvesters. Conclusion: Without the current substantial international donor subsidies, sustainable harvest cannot be sustained. What is required to supply the current and future market is to develop separate, traceable P. africana bark supply chains based on cultivated stocks. On-farm production would benefit thousands of small-scale farmers cultivating P. africana, including local women, for whom wild harvesting is too onerous. This change requires CITES and EU support and would catalyze P. africana cultivation in across several montane African countries and Madagascar, increasing farm-gate prices to harvesters compared to economic returns from wild harvest. Graphical abstract: